PEMBENTUKAN KARAKTER ANAK USIA DINI MELALUI KEGIATAN MENDONGENG DENGAN MEDIA BUKU CERITA BERGAMBAR DI TK PARAMAWANGSA DENPASAR UTARA - Sriani Ni Wayan; Aria Prima Dewi PF Kadek; Luwih I Made (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
Character building in early childhood can be done in various ways, one of which is through storytelling. Storytelling activities using illustrated storybook media such as this have long been used by teachers in Paramawangsa Kindergarten and have shown results that are visible from children who have empathy are left to behave politely and one of the values of character education that has been successfully cultivated by children -children are social care values. The formulation of the problem that will be discussed among others (1) How is the process of Character Formation of Early Childhood Through Activity Storytelling with Media Book Picture Story in TK Paramawangsa Denpasar Utara? (2) What are the constraints faced by the teacher when the Early Childhood Character Formation Activity Through Storytelling with Media Books Picture Stories at Paramawangsa Kindergarten North Denpasar? (3) What are the advantages of Character Formation of Early Childhood Through Activity Storytelling with Media Book Picture Story in TK Paramawangsa Denpasar Utara? The formation of character through storytelling activities is very very suitable to be applied to early childhood so that children are more easily understand the contents of the fairy tale.